Prevalence of attention deficit hyperactivity disorder symptoms in patients with schizophrenia. (13th August 2018) - Arican, I.; Bass, N.; Neelam, K.; Wolfe, K.; McQuillin, A.; Giaroli, G.
Abstract : Objective: To investigate the frequency of childhood and adult attention deficit hyperactivity disorder (ADHD) symptoms in a cohort of patients with schizophrenia (SCZ). Methods: A systematic review was conducted to evaluate existing evidence. Two self‐report questionnaires were used to investigate adult ADHD and childhood ADHD symptoms in 126 patients with ICD‐10 diagnoses of SCZ. Results: Five studies were included in the systematic review, with the prevalence of childhood and adult ADHD in SCZ subjects ranging between 17–57% and 10–47% respectively. Within our cohort, 47% of patients reported positive screening for ADHD symptoms either in childhood or adulthood. 23% reported symptomatology consistent with both childhood and adult ADHD. Conclusions: We demonstrate a greater presence of ADHD symptomatology in SCZ compared to that reported for ADHD in the general population. Our findings highlight the importance of improved clinical assessment and treatment considerations in a subgroup of patients with SCZ.